Almeidaite, Pb(Mn, Y)Zn2(Ti, Fe3+)18O36(O, OH)2, a new crichtonite-group mineral, from Novo Horizonte, Bahia, Brazil. (2nd January 2018) - Menezes Filho, Luiz A. D.; Chukanov, Nikita V.; Rastsvetaeva, Ramiza K.; Aksenov, Sergey M.; Pekov, Igor V.; Chaves, Mário L. S. C.; Richards, R. Peter; Atencio, Daniel; Brandão, Paulo R. G.; Scholz, Ricardo; Krambrock, Klaus; Moreira, Roberto L.; et al.
Abstract: Almeidaite (IMA 2013-020), ideally Pb(Mn, Y)Zn2(Ti, Fe 3+ )18 O36 (O, OH)2, from Novo Horizonte, Bahia, Brazil, occurs in association with quartz, rutile, anatase, hematite, kaolinite, muscovite, xenotime-(Y) and bastnaesite-(La). Almeidaite forms isolated, black, opaque, sub-metallic, platy crystals flattened on [0001], measuring up to 30 mm 6 30 mm 6 6 mm in size, dominated by the basal pinacoid {0001}, which is bounded by various, mostly steep, rhombohedra and the hexagonal prism {1120}. Most of the crystals are multiply twinned, with non-planar contact surfaces that are approximately parallel to the c axis. The streak is brown. Reflectance values are [( R o, R e ) λ (nm)]: (12.78, 15.39) 470; (12.86, 15.43) 546; (12.91, 15.55) 589; (13.04, 15.75) 650. The empirical formula is (Pb0.59 Sr0.12 Ca0.04 La0.03 )Σ0.78 (Mn0.54 Y0.46 )Σ1.00 Zn1.43 (Ti13.02 Fe4.98 3+ )Σ18.00 (Fe0.32 3+ Mn0.15 )Σ0.47 [O37.18 (OH)0.82 ]Σ38.00 . It is trigonal, space group R 3, with the unit-cell parameters a = 10.4359(2), c = 21.0471(4) Å, V = 1985.10(7) Å 3 and Z = 3. The crystal structure was solved ( R 1 = 0.039) using 2110 unique reflections with I > 3σ( I ). Almeidaite is a member of the crichtonite group with Pb dominant in the A site (with 12-fold coordination) and Zn dominant in the T site (with 4-fold coordination). It is a Zn analogue of senaite and a Pb analogue of landauite. The mineral is named after Professor Fernando Flávio Marques de Almeida (1916–2013).